A Study of Hyponatremia as a Predictor of Severity in Pediatric Community Acquired Pneumonia (Cap) In Children Aged 2 Months – 5 Years Admitted To a Tertiary Care Center - Dr. Thirupathi Madasu; Dr. S.Srikanth; Dr. T.Radha Kishan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
children <5 years worldwide, and simple, inexpensive biomarkers that predict severity are urgently needed. Hyponatremia has been linked to adverse outcomes in adult CAP, but pediatric data are sparse Methods: In this cross sectional cohort study (July 2022 – January 2024) we enrolled 200 radiographically confirmed CAP cases (2 months–5 years) admitted to the respiratory ICU of Niloufer Hospital, Hyderabad. Serum sodium measured within 6 h of admission was classified as normal (≥135 mmol/L), mild (130–134), moderate (126–129) or severe (≤125). WHO 2014 two tier severity criteria (pneumonia vs severe pneumonia) were applied [4] Primary outcomes were incidence of hyponatremia and its association with severity indicators (WHO class, shock, mechanical ventilation, length of stay, and mortality). Results: Incidence of hyponatremia was 41% (mild 24.2%, moderate 16.7%; no severe cases). Hyponatremia was significantly more common in infants (<1 y) than in older children (61% vs 26%, p < 0.001). Moderate hyponatremia clustered in severe pneumonia (38.6% vs 3.9% in non severe, p < 0.001), in children with shock (44.4% vs 8.6%), and in those needing mechanical ventilation (54.5% vs 12.8%). Hospitalization >7 days (OR 9.7, 95% CI 4.5–21) and in hospital death (OR 11.8, 95% CI 2.1–66) were strongly associated with moderate hyponatremia. Conclusions: Hyponatremia on admission is common and independently predicts clinical severity and short term outcomes in pediatric CAP. A serum sodium cut off <130 mmol/L may serve as a low cost triage tool in resource limited settings.